The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1515/humor.2008.016
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and perceived humor

Abstract: Without an objective metric for identifying how funny humorous material “really” is, a person may rely on external information in evaluating the humor of a particular humorous joke. In two experiments, we examined the effect of expectations on participants' ratings of jokes. When participants received a message that jokes had previously been rated as either funny or unfunny, they rated the jokes accordingly. In addition, participants who were told less plausible messages about the jokes (“hysterically funny” o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…In summary, it is argued that prior exposure to the named comedian primes an expectancy of forthcoming humor; this expectancy influences humor ratings. These findings are consistent with Wimer and Beins (2008), who showed that priming humor expectations through joke ratings can influence cognitive humor. The current study may explain why new comics need to "win over the audience" whereas established comedians can rely upon the expectation of humor derived from past exposures.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…In summary, it is argued that prior exposure to the named comedian primes an expectancy of forthcoming humor; this expectancy influences humor ratings. These findings are consistent with Wimer and Beins (2008), who showed that priming humor expectations through joke ratings can influence cognitive humor. The current study may explain why new comics need to "win over the audience" whereas established comedians can rely upon the expectation of humor derived from past exposures.…”
supporting
confidence: 91%
“…Furthermore, Wimer and Beins (2008) have shown that exposure to prior ratings of a joke can influence the subsequent appraisal of the joke. In Experiment 1 of their study, the authors presented participants with a booklet of jokes in which each joke had been described as hysterically funny, very funny, neutral, not very funny, or horribly unfunny.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the frequency and duration of smiling and laughter in response to humorous stimuli is impacted by the presence of a laughing versus a nonlaughing model person. Further factors, such as the responsiveness of the companion, the seating position, and proximity to the companion, as well as eye contact, age difference between the companion and the subject, whether groups of strangers or friends are together, and the group size have been investigated and shown to be influential (i.e., leading to more overt amusement responses; e.g., Devereux and Ginsburg 2001;Levy and Fenley 1979;Wimer and Beins 2008). Furthermore, the current mood influences the effects of the increased amusement due to the presence of a companion: Only high state cheerful individuals smiled more by the mere presence of another person, but this was not so for individuals that were not in a cheerful mood (e.g., Deckers 2007).…”
Section: Introductionmentioning
confidence: 99%